Editorial. (March 2013) - Alderman, Lyn; Clinton, Janet; Harvey, Graeme
For the first edition of the Evaluation Journal of Australasia for 2013, I would like to welcome Associate Professor Janet Clinton and Lyn Alderman as members of the editorial team. Both Janet and Lyn bring a depth of experience, expertise and a great deal of enthusiasm for evaluation and in the continued development of EJA. Currently, Associate Professor Janet Clinton is Director of the Centre for Program Evaluation at the University of Melbourne and Lyn Alderman is the Manager of Academic Quality and Standards at Queensland University of Technology. Lyn is also the Chair of the AES Journal and Publications Working Group.